2021
DOI: 10.1590/1518-8345.5435.3503
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and beliefs about acute coronary syndrome among patients with type 2 diabetes

Abstract: Objective: to evaluate the knowledge, attitudes, and beliefs of Guyanese individuals with type 2 diabetes regarding acute coronary syndrome and explore associations between these measures and the population’s sociodemographic and clinical characteristics. Method: cross-sectional study conducted in Linden, Guyana, with sixty type 2 diabetics, interviewed using a sociodemographic and clinical questionnaire and the Acute Coronary Syndrome-Response Index. The Mann-Whitney test was used to assess potential differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…From a clinical perspective, diabetic participants were more likely to be knowledgeable about ACS and is supported by several LMIC studies [36]. Conversely, in study elsewhere diabetic patients identi ed as having lower knowledge of ACS symptoms [37]. Diabetes self-management is complex, and patients are more likely to experience atypical ACS symptoms which can potentially result in poor symptom recognition as other studies have reported [38].…”
Section: Discussionmentioning
confidence: 61%
“…From a clinical perspective, diabetic participants were more likely to be knowledgeable about ACS and is supported by several LMIC studies [36]. Conversely, in study elsewhere diabetic patients identi ed as having lower knowledge of ACS symptoms [37]. Diabetes self-management is complex, and patients are more likely to experience atypical ACS symptoms which can potentially result in poor symptom recognition as other studies have reported [38].…”
Section: Discussionmentioning
confidence: 61%
“…From a clinical perspective, diabetic participants were more likely to be knowledgeable about ACS and is supported by several LMIC studies [37]. Conversely, in study elsewhere diabetic patients identified as having lower knowledge of ACS symptoms [38]. Diabetes self-management is complex, and patients are more likely to experience atypical ACS symptoms which can potentially result in poor symptom recognition as other studies have reported [39].…”
Section: Discussionmentioning
confidence: 69%
“…The self-confidence among coronary heart disease patients found still lo like vulnerability feeling, advantages of preventing heart attack, still found patients feel constrained in self-care (Athbi & Hassan, 2019). Self-confidence coupled with a lack of knowledge and attitudes in patients diagnosed with ischemia is associated with delays in seeking help (Johnson et al, 2021). Self-Self-confidence of CHD patients is the role of self-care to help prevent recurrences such as selfefficacy in diet, self-eefficacy in exercise, and self-efficacy in smoking cessation (Qi et al, 2018).…”
Section: Attributing Definitionmentioning
confidence: 99%